Detection and description of a novel Psychrobacter glacincola infection in some Red Sea marine fishes in Hurghada, Egypt - Mohamed Raafat El-Sayed; Arafah M. Emam; Ahmed Elsayed Osman; Mohamed Abd El-Aziz Ahmed Abd El-Galil; Haitham Helmy Sayed (BMC Veterinary Research, 2023)
Abstract An important food-producing sector in Egypt is aquaculture and fisheries; however, several pathogenic microorganisms lead to high mortalities and significant economic losses. The occurrence of Psychrobacter glacincola infection among 180 wild marine fishes collected from the Red sea at Hurghada, Egypt were investigated in the present study. The disease prevalence rate was 6.7%. The recovered isolates were subjected to biochemical and molecular identification. The study also investigated pathogenicity and the antibiogram profile of the recovered isolates. The clinical examination of the infected fish revealed various signs that included lethargy and sluggish movement, hemorrhages and ulcers on the body and the operculum, scale loss, and fin congestion and rot, especially at the tail fin. Furthermore, during postmortem examination, congestion of the liver, spleen, and kidney was observed. Interestingly, 12 isolates were recovered and were homogenous bacteriologically and biochemically. The phylogenetic analysis based on 16S rRNA gene confirmed that MRB62 identified strain was closely related the genus Psychrobacter and identified as P. glacincola and was pathogenic to Rhabdosargus haffara fish, causing 23.3% mortality combined with reporting a series of clinical signs similar to that found in naturally infected fishes. The present study also showed that P. glacincola isolates were sensitive to all antibiotics used for sensitivity testing. Our findings add to the body of knowledge regarding the occurrence of pathogenic P. glacincola infection in Egyptian marine fishes and its potential effects on fish. Future large-scale surveys exploring this bacterium among other freshwater and marine fishes in Egypt would be helpful for the implementation of effective strategies for the prevention and control of this infection are warranted.